Stress Management And Blood Glucose Control Among Patients With Type 2 Diabetes Mellitus: Implications For Nursing Management - Erik Estrada; Hardono; Hana Zumaedza Ulfa; Giri Susanto; Chusairil Pasha (Journal of Nursing Management Innovations, 2025)
Research background: Diabetes Mellitus is a chronic metabolic disease characterized by hyperglycemia due to impaired insulin function. Stress is one of the psychological factors that can increase blood glucose levels through hormonal mechanisms, especially through increased cortisol and catecholamines. Stress management is an important part of the non-pharmacological treatment of Diabetes Mellitus patients.Aim : This study aims to analyze the relationship between stress management and blood glucose levels in patients with type 2 Diabetes Mellitus at Pringsewu Hospital.Methods: This study used an analytical quantitative design with a cross-sectional approach. The sample amounted to 70 respondents who were selected using the purposive sampling technique. Stress management data was collected using a Likert scale questionnaire, while blood glucose levels were checked using a glucometer. Bivariate analysis uses a Gamma correlation test.Results: Results showed that 40% of respondents had poor stress management and 60% had uncontrolled blood glucose levels. The gamma test showed a significant association between stress management and blood glucose levels (p value = 0.000), suggesting that the better the stress management skills, the more controlled the patient's blood glucose levels.Conclusion: Stress management abilities have been shown to have a significant influence on glycemic control in patients with type 2 Diabetes Mellitus. Therefore, the application of stress management interventions needs to be integrated into conducting holistic care in healthcare facilities to support improving patients' quality of life